To See with a Better Eye : A Life of R. T. H. Laennec - Duffin, Jacalyn (Book collections on Project MUSE., 2014)
Rene Theophile Hyacinthe Laennec (1781-1826) is best known for his invention of the stethoscope, one of medicine's most powerful symbols. Histories, novels, and films have cloaked his life in hagiography and legend. Jacalyn Duffin's fascinating new biography relies on a vastly expanded foundation of primary source material, including thousands of pages of handwritten patient records, lecture notes, unpublished essays, and letters. She situates Laennec, the scientist and teacher, within the broader social and intellectual currents of post-Revolutionary France. Her work uncovers a complex cha.